2000
DOI: 10.1088/0741-3335/42/5/308
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the interaction of a plasma stream with neutral gas: evidence of plasma loss through molecular-activated recombination

Abstract: We describe an experiment, the UMIST Linear System (ULS), in which a hydrogen plasma stream, guided by a longitudinal magnetic field, is injected through a diaphragm containing an orifice into a separately-pumped target chamber in which the neutral hydrogen pressure can be raised to a maximum of 8 mTorr. The stream is about 6 mm in diameter, has an electron temperature of up to 15 eV and an ion flux of 3 × 10 18 s −1 ; it is supersonic with Mach number up to M ≈ 3. We have studied both the passage of the strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…In the absence of the downstream dipole field structure it would be expected that this plasma would propagate along the solenoidal confining field until it encountered the end target plate of the gas target chamber. Previous studies at low target chamber gas pressures similar to those used in these studies have indicated that any reductions in the peak density or temperature occur over characteristic axial scale lengths >1 m with the beam width (FWHM) remaining constant along the whole length of the target chamber [10]. This is consistent with the expected collisional scale lengths for these plasmas: the ion-ion mean free path is of the order of 10 m and the typical ion-neutral mean free path is approximately 25 cm, an order of magnitude greater than the ion Larmor radius.…”
Section: Upstream Plasma Beam Characteristicsmentioning
confidence: 89%
See 2 more Smart Citations
“…In the absence of the downstream dipole field structure it would be expected that this plasma would propagate along the solenoidal confining field until it encountered the end target plate of the gas target chamber. Previous studies at low target chamber gas pressures similar to those used in these studies have indicated that any reductions in the peak density or temperature occur over characteristic axial scale lengths >1 m with the beam width (FWHM) remaining constant along the whole length of the target chamber [10]. This is consistent with the expected collisional scale lengths for these plasmas: the ion-ion mean free path is of the order of 10 m and the typical ion-neutral mean free path is approximately 25 cm, an order of magnitude greater than the ion Larmor radius.…”
Section: Upstream Plasma Beam Characteristicsmentioning
confidence: 89%
“…The experimental studies were carried out on a linear plasma confinement device LinX, a modified version of the ULS device [10] previously used to study plasma-neutral interactions of relevance to tokamak divertors [11,12]. The plasma in this system consists of a supersonic plasma beam (Mach number>3) with peak densities and temperatures in the range 10 17 -10 19 and 5-7 eV, respectively.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…A scaled laboratory experiment has the potential to deliver physical insights and to offer observational signatures which can be examined, to establish whether they are consistent or not with the in-situ space data. The Plasma Wind Tunnel [25] used here shares the same phenomenological regime as the subset of analogous space parameters. These are: the plasma is collisionless, the bulk flow speed is supersonic and the electrons are magnetized but the ions are not.…”
mentioning
confidence: 99%
“…7 As such, the experiment combines the high ion flux capabilities of Pilot-PSI 8 with low background pressure and large beam diameter to reach the strongly coupled regime. It should be mentioned that differential pumping has been used before on linear plasma generators, [9][10][11][12] in which it was used to vary the neutral pressure in the target chamber by means of gas puff to study detached plasmas as a possible way to mitigate the power flux to the divertor. However, the electron density and fluxes in these machines were more than an order of magnitude lower as compared to the conditions at the FIG.…”
mentioning
confidence: 99%